2001
DOI: 10.5034/inquiryjrnl_38.1.73
|View full text |Cite
|
Sign up to set email alerts
|

Costs in the Last Year of Life in the Netherlands

Abstract: The costs of health care in the last year of life are a subject of debate and myth. Expensive interventions at the end of life often are blamed for the rapid increase in health care spending, but evidence about the existence of such exceptionally high expenditures at the end of life is rare and faulty. This investigation examines the development and composition of health care costs at the end of life for all age groups in The Netherlands. In contrast with earlier studies, this research analyzes both acute care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
16
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 13 publications
3
16
0
1
Order By: Relevance
“…Although non-surviving patients contributed a substantially greater per person total hospitalization cost than surviving patients during a 1-year period, the amount of total charges for all patients who did not survive their final hospitalization accounted for 16% of all expenditures (US$ 123.8 million). These results are consistent with the findings of previous studies: health care expenditures in the last year of life account for a small fraction of the total expenditures in Japan (12%) [9] and the Netherlands (10% [26] and 11% [27]). …”
Section: Discussionsupporting
confidence: 95%
“…Although non-surviving patients contributed a substantially greater per person total hospitalization cost than surviving patients during a 1-year period, the amount of total charges for all patients who did not survive their final hospitalization accounted for 16% of all expenditures (US$ 123.8 million). These results are consistent with the findings of previous studies: health care expenditures in the last year of life account for a small fraction of the total expenditures in Japan (12%) [9] and the Netherlands (10% [26] and 11% [27]). …”
Section: Discussionsupporting
confidence: 95%
“…Instead, several studies have found that health care costs tend to be associated with the end of life: the 6% of Medicare recipients who die in a given year account for 28% of Medicare expenditures, a finding that has remained stable from the late 1970s to the mid 1990s (Hogan et al, 2001;Lubitz and Prihoda, 1984;Lubitz and Riley, 1993;Riley et al, 1987). Similar findings have been reported for long term care (Stooker et al, 2001). Thus, the association between age and health expenditure may well be an artefact of a stronger relationship between proximity to death and health expenditure.…”
Section: Introductionsupporting
confidence: 80%
“…For example, in the US, it has been consistently shown that approximately 6% of Medicare recipients who die in a particular year account for approximately 28% of HCE under that scheme [16][17][18]. Similar results have been reported for longterm care [19].…”
Section: Introductionsupporting
confidence: 59%